BubR1 Insufficiency Inhibits Neointimal Hyperplasia Through Impaired Vascular Smooth Muscle Cell Proliferation in Mice. Issue 2 (February 2015) - Kyuragi, Ryoichi; Matsumoto, Takuya; Harada, Yui; Saito, Satoru; Onimaru, Mitsuho; Nakatsu, Yoshimichi; Tsuzuki, Teruhisa; Nomura, Masatoshi; Yonemitsu, Yoshikazu; Maehara, Yoshihiko
<x xml:space="preserve">Abstract</x> Objective— BubR1, a cell cycle–related protein, is an essential component of the spindle checkpoint that regulates cell division. Mice with BubR1 expression reduced to 10% of the normal level display a phenotype characterized by progeria; however, the involvement of BubR1 in vascular diseases is still unknown. We generated mice in which BubR1 expression was reduced to 20% (BubR1L/L mice) of that in wild-type mice (BubR1+/+) to investigate the effects of BubR1 on arterial intimal hyperplasia. Approach and Results— Ten-week-old male BubR1L/L and age-matched wild-type littermates (BubR1+/+) were used in this study. The left common carotid artery was ligated, and histopathologic examinations were conducted 4 weeks later. Bone marrow transplantation was also performed. Vascular smooth muscle cells (VSMCs) were isolated from the thoracic aorta to examine cell proliferation, migration, and cell cycle progression. Severe neointimal hyperplasia was observed after artery ligation in BubR1+/+ mice, whereas BubR1L/L mice displayed nearly complete inhibition of neointimal hyperplasia. Bone marrow transplantation from all donors did not affect the reconstitution of 3 hematopoietic lineages, and neointimal hyperplasia was still suppressed after bone marrow transplantation from BubR1+/+ mice to BubR1L/L mice. VSMC proliferation was impaired in BubR1L/L mice because of delayed entry into the S phase. VSMC migration was unaffected in these BubR1L/L mice. p38 mitogen–activated protein kinase–inhibited VSMCs showed low expression of BubR1, and BubR1-inhibited VSMCs showed low expression of p38. Conclusions— BubR1 may represent a new target molecule for treating pathological states of vascular remodeling, such as restenosis after angioplasty.